2009
DOI: 10.1002/cncr.24537
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor in the management of hepatocellular carcinoma

Abstract: The consumption of antidepressants, especially selective serotonine reuptake inhibitors (SSRI) has been increasing. Because a large fraction of the population is exposed, even a small excess of risk with respect to cancer should be considered. We carried out a record linkage study in Finland utilizing nationwide databases of reimbursed medication and cancer. The study population included all antidepressant drug (AD) users in Finland who had purchased at least 1 prescription between 1998 and 2005, and who had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 71 publications
5
93
0
2
Order By: Relevance
“…Interestingly, VEGF expression has been reported to be highest in cirrhotic regions of the liver which surround HCC tumors in human patients (39), and agents are currently being designed to target both tumor and surrounding liver tissue as both appear critical in tumor formation and propagation (40,38). Administering a single injection of MRX34 inhibited mRNA expression of MAPKAPK2, NFATC3, and MAPK1, which all function within the VEGF pathway (41). The ability to diminish angiogenesis via the VEGF pathway is a likely contributor to the efficacy observed in our mouse models of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, VEGF expression has been reported to be highest in cirrhotic regions of the liver which surround HCC tumors in human patients (39), and agents are currently being designed to target both tumor and surrounding liver tissue as both appear critical in tumor formation and propagation (40,38). Administering a single injection of MRX34 inhibited mRNA expression of MAPKAPK2, NFATC3, and MAPK1, which all function within the VEGF pathway (41). The ability to diminish angiogenesis via the VEGF pathway is a likely contributor to the efficacy observed in our mouse models of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…There are three main subtypes of VEGF receptors: VEGFR-1, VEGFR-2, and VEGFR-3 (27). Binding of ligand to one of these receptors results in dimerization and auto phosphorylation of the intracellular tyrosine sites.…”
Section: Vegf Pathwaymentioning
confidence: 99%
“…These phosphorylated tyrosine regions then serve as docking sites for a variety of signal transduction proteins. The role of VEGF1 signaling has not been completely established but the most current supported theory is that VEGF1 activation plays a major role in the modulation of VEGF2 (27). Research has also shown that VEGF1 positive cells, which are derived from the bone marrow, might play a substantial role in different types of tumor progression (28).…”
Section: Vegf Pathwaymentioning
confidence: 99%
See 2 more Smart Citations